Experiences Building Graphics Literacy Skills: Interviews With Teachers and Students. (November 2021) - Rosenblum, L. Penny; Zebehazy, Kim T.; Gage, Nicholas; Beal, Carole R.
Introduction: Participants' perspectives are valuable in evaluating the effectiveness of an intervention. Methods: Interviews were conducted with teachers of students with visual impairments and students who completed an intervention designed to build graphics literacy skills. Results: Six themes were identified with corresponding subthemes. The intervention was reported to build students' graphics literacy skills. Discussion: Some students were able to generalize the strategies they learned to academic classes. Higher-level thinking skills challenged some students. Implications for practitioners: A systematic approach beginning early can increase students' graphics literacy skills. Teachers should provide ongoing opportunities for thinking and regulation of learning.